2020
DOI: 10.1002/jppr.1607
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Nigerian final year undergraduate students of the adequacy of the pharmacy curriculum for mental health care

Abstract: Background There is growing concern about the adequacy of undergraduate curricula in schools of pharmacy worldwide regarding mental health. In Nigeria, both Bachelor and Doctor of Pharmacy degrees (BPharm and PharmD, respectively) are offered, but little is known about the scope of mental health care in either curriculum. Aim This study evaluated the perceptions of final year undergraduate students regarding the adequacy of the pharmacy curriculum in mental health care and their preparedness for a career in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, another study found a gross level of dissatisfaction among final year pharmacy students with the adequacy of their training to offer mental health services. This study, interestingly, included as participants, students from both the Doctor of Pharmacy (PharmD) and Bachelor of Pharmacy (B.Pharm) programs—which are the two extant pharmacy curricula in Nigeria [ 11 ].…”
Section: Commentarymentioning
confidence: 99%
“…Furthermore, another study found a gross level of dissatisfaction among final year pharmacy students with the adequacy of their training to offer mental health services. This study, interestingly, included as participants, students from both the Doctor of Pharmacy (PharmD) and Bachelor of Pharmacy (B.Pharm) programs—which are the two extant pharmacy curricula in Nigeria [ 11 ].…”
Section: Commentarymentioning
confidence: 99%
“…However, many felt it was insufficient, leaving them unprepared for practicing in a mental health facility or managing the diversity of mental illnesses presentations —both skill- and emotional-wise. Similarly, a study amongst Nigerian pharmacy students noted the majority of PharmD and BSc students felt the undergraduate curriculum did not adequately prepare them to manage mental health patients and reported that there was insufficient exposure to real practical experiences [ 13 ]. There are also reports in the literature on how these educational gaps have been addressed by some pharmacy schools, such as: including classroom instruction that foster better understanding of mental illnesses through in-depth discussions, sessions instructed by mental healthcare professionals, counselling sessions with simulated patients, and including interactions with mental health consumers [ 9 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the authors deemed the rotation to have caused no major change on students’ social distance from patients with mental illness, they reported an overall improvement in the students’ attitudes towards schizophrenia, suicide prevention, and pharmaceutical care provision in this population [ 11 ]. More recently, similar studies conducted in the USA and Nigeria showed mixed findings on the benefits of mental health rotations on the students’ attitudes towards people with mental illnesses [ 12 , 13 ]. However, there is limited qualitative research on PharmD graduates’ opinions and perceived preparedness for the provision of pharmaceutical care to this population after completing a clinical rotation in psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…However, many felt they were still not prepared to practice in a mental health facility-both skill-wise and emotionally-wise. Similarly, a study in Nigerian pharmacy students noted the majority of PharmD and BSc students felt the undergraduate curriculum did not adequately prepare them to manage mental health pharmacy and did not provide enough exposure to real-life practice [30]. There are some reports in the literature on how these gaps have been addressed by other pharmacy schools, such as including classroom instruction that foster a deeper understanding of mental illness, and targeting pharmacy students' attitudes toward mental illness by including patients' experiences with mental illness via mental health consumers [9,31,32].…”
Section: Discussionmentioning
confidence: 99%